2010
DOI: 10.1158/0008-5472.can-09-3108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screen Identifies Insulin-like Growth Factor Binding Protein 5 as a Modulator of Tamoxifen Resistance in Breast Cancer

Abstract: Tamoxifen resistance is one of the overarching challenges in the treatment of patients with estrogen receptor (ER)-positive breast cancer. Through a genome-wide RNA interference screen to discover genes responsible for tamoxifen resistance in vitro, we identified insulin-like growth factor binding protein 5 (IGFBP5) as a determinant of drug sensitivity. Specific knockdown of IGFBP5 by retroviral infection with short hairpin RNAexpressing cassette in MCF7 human breast cancer cells (pRS-shIGFBP5) conferred tamox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 16 publications
1
52
0
Order By: Relevance
“…Previous in vitro studies have aimed to elucidate the role of IGF-1R in breast cancer resistance. A gene that confers resistance to tamoxifen is for IGF binding protein 5 (IGFBP5) (75). IGFBP5 is a secreted protein that inhibits growth factor binding to IGF-1R (76).…”
Section: Igf-1rmentioning
confidence: 99%
“…Previous in vitro studies have aimed to elucidate the role of IGF-1R in breast cancer resistance. A gene that confers resistance to tamoxifen is for IGF binding protein 5 (IGFBP5) (75). IGFBP5 is a secreted protein that inhibits growth factor binding to IGF-1R (76).…”
Section: Igf-1rmentioning
confidence: 99%
“…For example, IGFBP-5 expression has recently been shown to be associated with increased survival times in breast cancer patients as well as being responsible for maintaining sensitivity to tamoxifen (Ahn et al , 2010). In addition, overexpression of IGFBP-5 in MCF-7 xenografts inhibited tumour development in mice (Ahn, Elwi, 2010) whilst recent studies have demonstrated a tumour suppressor role for IGFBP-5 in ovarian cancer cells (Rho et al , 2008) in osteosarcoma (Su et al , 2011) and in breast cancer after foetal alcohol exposure (Polanco et al , 2010). An intriguing relationship between IGFBP-5 and tumour dormancy has also been described.…”
Section: Igfbp-5 and Cancermentioning
confidence: 99%
“…On the other hand, IGFBP5 expression has been found to correlate with prognosis, clinical outcome (Daigeler et al, 2010), survival (Ahn et al, 2010), response to therapy (Yamashita et al, 2009), and drug resistance (Taylor et al, 2010), either negatively or positively. IGFBP5 is one of the genes that has been shown to predict the prognosis of primary breast tumors in reverse tamoxifen resistance (Ahn et al, 2010). Moreover, lower expression levels of IGFBP5 are reported to be associated with shorter overall survival after tamoxifen (TAM) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked insulin-like growth factor (IGF)-binding protein 5 (IGFBP-5) to metastasis by revealing increased IGFBP-5 expression in metastatic patients (Pekonen et al, 1992;McGuire et al, 1994;Huynh, 1998;Mita et al 2007). One study showed IGFBP5 expression is inversely related with tumorogenesis of breast cancer (Polanco et al, 2010), where in another study, IGFBP-5 is shown to be associated with increased survival of breast cancer patients (Ahn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%